Two new species of Telipogon (Orchidaceae: Oncidiinae) from Costa Rica - Bogarín Chaves, Diego Gerardo 1982-
The Neotropical genus Telipogon (Oncidiinae), comprising approximately 250 species, exhibits remarkable species diversity in the humid, montane forests of southern Central America and the Tropical Andes. Telipogon, when broadly defined, encompasses both the large-flowered species that mimic tachinid flies and the small-flowered species formerly classified under Stellilabium. In Costa Rica, this genus includes 55 species, with 16 classified as small-flowered species. While the large-flowered species of Telipogon (in the strict sense) have been taxonomically revised, the small-flowered species have yet to be the subject of a thorough taxonomic revision. Our research aims to partially fill this gap by focusing on a comparative morphological analysis of two novel small-flowered Telipogon species. We describe and illustrate Telipogon lateritius and T. muntzii, both discovered in the humid mid-elevation forest of the Caribbean watershed in Cordillera de Talamanca, Costa Rica. Telipogon lateritius is notable for its distinctive brick-colored flowers, featuring sepals, petals, and lips striped in chestnut brown; the lateral sepals connate into a triangular-ovate synsepal, complemented by sparse, stiff pubescence at the base of the lip. Telipogon muntzii, although closely resembling T. anacristinae, differs in its unique olive-green flowers, sparse trichomes on the lip, narrowly oblong lateral lobes of the column, and a helmet-shaped median lobe of the column exclusively covered by simple trichomes. This study provides new additions for a future taxonomic revision of Telipogon in Costa Rica.